PERJANJIAN DALAM PERKAWINAN MENURUT PUTUSAN MAHKAMAH KONSTITUSI RI NO. 69/PUU-XIII/2015 DAN PENETAPAN PENGADILAN NEGERI TANGERANG NO.269/PEN.PDT.P/2015/PN.TNG - Veren Abigail; Abdul Gan Abdulilah (Jurnal Hukum Adigama, 2019)
According to the Marriage Law Article 29 the marriage agreement is made before or at the time of marriage. But in October 2016 the Constitutional Court passed verdict No.69 / PUU-XIII / 2015 as a material test of Article 29 of the Marriage Law which with the ruling of the constitutional court the marriage agreement can be made before, at the time of marriage, even throughout the marriage. However, before the constitutional court issued the verdict, the Tangerang District Court issued a ruling stipulating the marriage agreement throughout the marriage, namely the decision No. 269 / PEN.PDT.P / 2015 / PN.TNG which the parties were mixed marriages couple. The problem discussed is what the judge considers in deciding the marriage agreement when there is no provision that the marriage agreement can be made throughout the marriage. The legal research method used is a normative research method. Based on the research’s result, the judge granted and stipulated the marriage agreement based on the Marriage Law Article 4 which states that the marriage agreement is possible to be changed as long as there is agreement between the two parties and does not harm the third party In conclusion, the judge did not decide in accordance with the law regulating at the time. The suggestion is that it is expected that the judge as a law enforcer can make a decision in accordance with the law regulating at that time. Because ideally the judge's decision must contain justice, legal certainty, and expediency.